Analysis and Parameter Optimum of a New 4-DOF 4PPaRR Parallel Mechanism - Huiping Li; Feng Ou (Jixie chuandong)
The parallel mechanism of four-degree-of-freedom (4-DOF) 4PPaRR is proposed. Then its topological characteristic of analysis 4PPaRR parallel mechanism is performed based on the theory of position and orientation characteristic (POC), and the degree of freedom and motion property are validated by it. The inverse kinematics of the mechanism is analyzed, and the workspace of the 4PPaRR parallel mechanism is solved by numerical method. Then a performance index is defined in order to analyze the rotational capacity of 4PPaRR parallel mechanism, The scale optimization of parallel mechanism size is carried out based on Grasshopper Optimization Algorithm（GOA）in the end. The research results show that the 4PPaRR parallel mechanism has larger workspace and rotation capability. The optimization results can provide a theoretical basis for later prototype development and trajectory planning.